Perceived Paternal Involvement, Relationship Satisfaction, Mothers' Mental Health and Parenting Stress: A Multi-Sample Path Analysis - deMontigny, Francine; Gervais, Christine; Pierce, Tamarha; Lavigne, Geneviève (Frontiers in Psychiatry, 2020)
Research has demonstrated the short- and long-term impacts of maternal mental health on children’s emotional and behavioral outcomes. It is thus important to better understand the antecedents of maternal depression and stress. The aim of this study was to determine whether the contribution of perceived paternal involvement to mothers’ mental health was mediated by relationship factors such as parenting alliance and dyadic adjustment. A second aim was to determine whether these relationships hold equally true in mothers of infants and young toddlers (0–24 months) and mothers of older children (25 months and older). Cross-sectional data were collected from 447 mothers. Mothers reported on their perceptions of paternal involvement with childcare responsibilities, dyadic adjustment, parenting alliance, parenting stress, and depression. Multi-sample path modeling analyses were conducted. Results revealed that perceived paternal involvement was positively related to both dyadic adjustment and parental alliance, that dyadic adjustment was negatively related to parenting distress and mothers’ depression, and that parenting alliance was negatively related to all three subscales of parenting stress and mothers’ depression. Results from the multi-sample analyses indicated that the pattern of relationships was the same in the two groups, but that the model was not invariant. The most notable difference was that parenting alliance was not a significant predictor of depression in the mothers of younger children. Important correlates of maternal mental health that were identified could be highly useful for psychological interventions designed for mothers and fathers.